Financial Vulnerability of the Hungarian Population: Empirical Results Based on 2018 Representative Data - Németh, Erzsébet; Zsótér, Boglárka; Béres, Dániel (Public Finance Quarterly, 2020)
The aim of this paper is to introduce a new method to measure Financial Vulnerability Index (FVI) based on OECD financial literacy survey, and to analyse the 2018 OECD survey data along FVI. The sample used in the article is representative for Hungary (sample size: 1,001). Our analysis sharply points out that although the growth of income reduces financial vulnerability, the higher disposable amount does not increase financial awareness. One of the key findings of the research is the identification of the correlations between financial attitudes and financial vulnerability. Our analysis shows that the difficulty of prolonging current desires is a significant factor underlying the development of financial vulnerability. Financially vulnerable population groups not only often struggle to make ends meet, but they also have difficulty controlling spending money.